Penerapan Pembelajaran Dengan Menggunakan Pendekatan Saintifik Terhadap Pemahaman Konsep Siswa Pada Materi Tekanan Pada Zat Cair - Leha Leha; Nurul Apsari; Novika Lestari (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2026)
This study aims to determine the effect of the application of a scientific approach on students' conceptual understanding of the material on pressure in liquids. The research method used is quantitative with a Nonequivalent (Pretest-Posttest) Control Group Design. The research sample consisted of students of class VII A (16 students) as the experimental class and VII B (18 students) as the control class at SMP Negeri 5 Sungai Tebelian. The research instrument was a multiple-choice test consisting of 25 questions given at the pretest stage before the scientific approach model was applied and the posttest after learning with a scientific approach was carried out which included four indicators of conceptual understanding: Drawing inferences, Classifying, Interpreting, and giving examples. Data analysis used normality, homogeneity, and t-test tests. The research data showed a significant difference between the experimental class and the control class. The average posttest score of the experimental class (71.25) was higher than the control class (51.56). The results of the Independent Sample T-Test showed a t value = -4.447 with sig. (2-tailed) = 0.0000984 < 0.05, which means H₀ is rejected and Ha is accepted. Thus, the scientific approach has been proven to have a positive effect on improving students' conceptual understanding of pressure in liquids.